2018
DOI: 10.5114/amsad.2018.79407
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotrophin-1 and leptin as cardiovascular risk markers in male patients with obstructive sleep apnea syndrome

Abstract: IntroductionElevated cardiotrophin-1 (CT-1) and leptin levels are important risk factors for cardiovascular diseases (CVDs). Obstructive sleep apnea syndrome (OSAS) has also been reported to increase this risk. The aim of this study is to evaluate serum concentrations of CT-1 and leptin in patients with OSAS and whether there is a possible association between CT-1, leptin and OSAS severity.Material and methodsFifty newly diagnosed OSAS patients and thirty nonapneic snoring subjects participated in this study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Then another 26 articles were excluded for the different reasons indicated in Figure 1 . As shown in Table 1 , three were conducted in China ( 18 , 29 , 45 ), five in the USA ( 14 , 34 , 42 ), four in Poland ( 19 , 21 , 31 ), nine in Turkey ( 11 , 13 , 20 , 32 , 35 , 38 , 44 , 46 ), five in Spain ( 12 , 22 , 37 ), one in Australia ( 23 ), three in India ( 24 , 40 ), three in Greece ( 26 , 30 ), three in Italy ( 33 , 41 ), one in Brazil ( 36 ), two in Belgium ( 43 ), one in Egypt ( 15 ). With regard to ethnicity, 33 studies were performed with Caucasians ( 11 14 , 19 23 , 26 , 30 35 , 37 , 38 , 41 44 , 46 ), 11 with Asians ( 18 25 , 29 , 39 , 40 , 45 ), and one with Latinos ( 36 ) of the 45 studies, 13 reported leptin levels in plasma ( 12 , 14 , 19 , 22 , 30 , 33 , 42 , 46 ), and 32 ( 11 , 13 , 15 , 20 , 21 <...>…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Then another 26 articles were excluded for the different reasons indicated in Figure 1 . As shown in Table 1 , three were conducted in China ( 18 , 29 , 45 ), five in the USA ( 14 , 34 , 42 ), four in Poland ( 19 , 21 , 31 ), nine in Turkey ( 11 , 13 , 20 , 32 , 35 , 38 , 44 , 46 ), five in Spain ( 12 , 22 , 37 ), one in Australia ( 23 ), three in India ( 24 , 40 ), three in Greece ( 26 , 30 ), three in Italy ( 33 , 41 ), one in Brazil ( 36 ), two in Belgium ( 43 ), one in Egypt ( 15 ). With regard to ethnicity, 33 studies were performed with Caucasians ( 11 14 , 19 23 , 26 , 30 35 , 37 , 38 , 41 44 , 46 ), 11 with Asians ( 18 25 , 29 , 39 , 40 , 45 ), and one with Latinos ( 36 ) of the 45 studies, 13 reported leptin levels in plasma ( 12 , 14 , 19 , 22 , 30 , 33 , 42 , 46 ), and 32 ( 11 , 13 , 15 , 20 , 21 <...>…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen are cross-sectional study ( 13 , 26 , 28 , 32 , 37 , 39 , 40 , 42 , 43 ). Thirty-one are case-control study ( 11 , 12 , 14 , 15 , 18 23 , 25 , 27 , 29 – 31 , 33 36 , 38 , 41 , 44 46 ). Nine studies included children ( 14 , 29 , 34 , 42 , 43 , 45 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also observed that serum leptin concentrations were significantly associated with HOMA-IR levels after adjustment for some confounding factors including maternal age, education, P-BMI, age at menarche, parity, abortion, WG in the third trimester of pregnancy, FBG, TG, TC, LDL-C, HDL-C and serum adipokine concentrations. Physiologically, leptin is synthesized and secreted from placental trophoblasts into the maternal circulation in considerable amounts during pregnancy [ 34 , 35 ] and the serum concentration of leptin was higher in pregnant women than that in nonpregnant women, with the peak occurring around the 28 th week of gestation. At the same time, the trend of IR [ 36 , 37 ] was similar to that of serum leptin concentration.…”
Section: Discussionmentioning
confidence: 99%
“…They are considered as risk factors for cardiovascular diseases. Specifically, CT-1 induces hypertrophy of cardiac myocytes in vitro and contributes to cardiomyopathies and heart failure [ 16 ]. Levels of both markers are significantly increased in patients with OSA compared to controls, and are significantly elevated in severe OSA compared to mild to moderate OSA [ 16 ].…”
Section: Chronic Intermittent Hypoxia and The Pathophysiology Of Atherosclerosismentioning
confidence: 99%